My father's shop - Ichikawa, Satomi (Kane/Miller Book Publisher, 2006)
"Come visit Mustafa in his favorite place in all of Morocco--his father's shop. Here amongst the beauriful rugs, is an entire world of colors, textiles, and languages..."-- Jacket.